ANALYSIS OF THE WORK ENVIRONMENT AND WORK MOTIVATION FOR EMPLOYEE PERFORMANCE - Daud Arifin (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the influence of work environment and work motivation on employee performance in a company. The sample used in this study consisted of 30 employees from various departments. Quantitative methods are applied by using questionnaires to collect data. The results showed that a good work environment had a significant positive effect on employee performance, with a regression coefficient of 0.45. In addition, work motivation has also been shown to have a significant effect, with a regression coefficient of 0.38. Simultaneous analysis showed that these two variables could explain 53.7% variation in employee performance. These findings emphasize the importance of creating a conducive work environment and effective motivational strategies to improve employee performance. This research provides valuable insights for management in an effort to improve employee productivity and job satisfaction. Recommendations for further research are also suggested to explore other factors that can affect employee performance in various industry contexts.